The Implementation Of Assessment In An Inclusive English Classroom - Siti Aisaturrohmi Mukassyafah; Dewi, Ni Luh Putu Eka Sulistia; A.A. Gede Yudha Paramartha (Al-Zayn : Jurnal Ilmu Sosial & Hukum, 2026)
This study aims to explore the implementation of assessment in inclusive classrooms for English language learning at SDN 1 Munduk. This study uses a descriptive qualitative research method with data collection techniques through observation, interviews, and documentation. The research subjects consisted of one fourth-grade English teacher and one student with learning difficulties studying in a regular inclusive classroom. The results showed that the teacher had implemented diagnostic, formative, and summative assessments with several forms of adjustments according to the students’ needs. In diagnostic assessments, the teacher tended to use the same assessment for all students to determine their initial abilities and learning needs. In formative assessment, the teacher differentiated assessments by simplifying tasks, providing clearer instructions, allowing extra time, and offering assistance during the assessment process. Additionally, the teacher planned adjustments for summative assessments while maintaining the same competency standards. These adjustments included reducing the number of questions, offering oral response options, simplifying the language of the questions, and providing support throughout the assessment. This study also identified several challenges in implementing assessments in inclusive classrooms, such as differences in student abilities within a single class, time constraints, a lack of training related to inclusive assessment, and the absence of a specific reporting system for students with learning difficulties. The study concluded that implementing assessments in inclusive classrooms requires flexibility, adjustments, and appropriate support so that all students can demonstrate their learning abilities optimally.